2003
DOI: 10.1152/japplphysiol.01043.2002
|View full text |Cite
|
Sign up to set email alerts
|

Level and duration of developmental hyperoxia influence impairment of hypoxic phrenic responses in rats

Abstract: Mitchell. Level and duration of developmental hyperoxia influence impairment of hypoxic phrenic responses in rats. J Appl Physiol 95: 1550-1559, 2003. First published June 20, 2003 10.1152 10. /japplphysiol.01043.2002 (1-4 wk of 60% O2) causes longlasting impairment of hypoxic phrenic responses in rats. We hypothesized that shorter or less severe hyperoxic exposures would produce similar changes. Hypoxic phrenic responses were measured in 3-to 5-mo-old, urethane-anesthetized rats exposed to 60% O2 for postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In that study, hyperoxia-treated rats increased ventilation only onethird as much as the untreated control group at similar arterial PO 2 . Similar observations have now been made for adult rats previously exposed to only 1-2 wk of 30 or 60% O 2 (7,10) or to 2 wk of intermittent exposure to 60% O 2 (21 or 60% O 2 at 1-h intervals; 10) in the early postnatal period; this plasticity does not differ between sexes (10, 33). The HCVR of adult rats is not altered by perinatal hyperoxia (56), indicating that this plasticity is specific to the hypoxic chemoreflex vs. a more general impairment of the respiratory system.…”
Section: Developmental Plasticity In Respiratory Control: Examplessupporting
confidence: 79%
See 1 more Smart Citation
“…In that study, hyperoxia-treated rats increased ventilation only onethird as much as the untreated control group at similar arterial PO 2 . Similar observations have now been made for adult rats previously exposed to only 1-2 wk of 30 or 60% O 2 (7,10) or to 2 wk of intermittent exposure to 60% O 2 (21 or 60% O 2 at 1-h intervals; 10) in the early postnatal period; this plasticity does not differ between sexes (10, 33). The HCVR of adult rats is not altered by perinatal hyperoxia (56), indicating that this plasticity is specific to the hypoxic chemoreflex vs. a more general impairment of the respiratory system.…”
Section: Developmental Plasticity In Respiratory Control: Examplessupporting
confidence: 79%
“…Furthermore, these effects of hyperoxia are unique to development because exposure to similar levels and durations of hyperoxia have no lasting effect on respiratory control if presented after the second postnatal week (6,56,57). The effects of developmental hyperoxia on normoxic ventilation are not consistent across studies, with different groups of rats showing either mild hyperventilation (10,56) or no persistent changes as adults (7,10).…”
Section: Developmental Plasticity In Respiratory Control: Examplesmentioning
confidence: 99%
“…Previous studies have shown that as little as one week exposure to 30–60% O 2 is sufficient to attenuate whole-nerve CSN and ventilatory responses to hypoxia into adulthood (Bavis et al, 2002; Bavis et al, 2003; Bisgard et al, 2003). Given the observed recovery of single-unit hypoxic responses, our data suggest that the impaired hypoxic responses observed in adult rats are not caused by decreased sensitivity of individual chemoreceptor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to hypoxia, which activates the carotid body and thus the central respiratory network, hyperoxia during the first 2 postnatal weeks, when the carotid body is maturing, blunts the chemosensitivity of the carotid body and impairs the ventilatory response to acute hypoxic challenge in the young as well as the adult (Bavis et al, 2003; Donnelly et al, 2009). As little as 3 to 5 days of hyperoxia significantly reduced presynaptic calcium response and catecholamine release from glomus cells, and it decreased postsynaptic afferent nerve excitability as well as its conduction velocity (Donnelly et al, 2009).…”
Section: Developmental Considerationsmentioning
confidence: 99%